The shepherd's crown - Pratchett, Terry (Pratchett, Terry. Discworld series (New York, N.Y.), 2016)
Deep in the Chalk, Tiffany Aching feels something stirring as an old enemy is gathering strength, and while the fairy horde prepares for invasion, she must summon all of the witches to stand with her to protect the land.